Optimalisasi Peran Sukuk dalam Meningkatkan Kinerja Industri Halal di Indonesia - Shafira, Alfina; Rizal, Sofyan; Aziz, Roikhan Mochamad; Hasan, Asyari (Balai Diklat Keagamaan Bandung, 2025)
This study explores the strategic role of sukuk (Islamic bonds) in advancing the performance of Indonesia's halal industry, which holds vast potential given the country’s large Muslim population. The purpose of this research is to identify how sukuk can be utilized as an effective Islamic financial instrument to support the growth of various halal sectors, including food, cosmetics, pharmaceuticals, tourism, and fashion. Employing a qualitative descriptive method through a literature review, this study synthesizes data from scholarly journals, institutional reports, and regulatory sources. The findings show that sukuk significantly contributes to the financing needs of the halal industry, particularly in infrastructure development, production capacity expansion, and market competitiveness. Furthermore, the integration of sukuk-based financing supports Indonesia’s vision to become a global hub for the halal economy. The study concludes that optimizing sukuk issuance and public awareness through multi-stakeholder collaboration—including government, Islamic scholars, financial practitioners, and industry players—is essential for accelerating the industry's performance. It is recommended that Indonesia strengthen policy frameworks, enhance halal certification efficiency, and encourage sukuk-backed investment mechanisms to boost national halal industry competitiveness.